Phytochemical analysis and antioxidant activity of different extracts of Lawsonia inermis: a mini review / Muhammad Khairul Aniq Khalid ... [et al.] - Khalid, Muhammad Khairul Aniq; Abdullah, Anas; Mohamed, Emida; Camalxaman, Siti Nazrina; Rambely, Azlin Sham; Haron, Norhisham (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Lawsonia inermis is a member of the Lythraceae family and is known as "Hinai" in Malaysia and "Henna" in India. It has many traditional medicinal and pharmaceutical properties. The extraction method and solvent determine the extraction yield and antioxidant activity from plants. Thus, the purpose of this review is to provide an overview on how different extraction solvents affect the phytochemical and antioxidant properties of L. inermis. The phytochemical constituents recorded in qualitative studies include carbohydrate, protein, amino acid, sterols, saponins, alkaloids, tannins, flavonoid, anthraquinones, terpenoids, steroids, phenols, reducing sugar, glycoside, cardioglycosides, and oils. The solvent such as methanol, ethanol, acetone, chloroform, and aqueous are commonly used for plant extraction. Rather than the bark and fruit parts of L. inermis, the leaves and flowers were widely used and reported to reveal many phytochemical constituents. Antioxidant activity of L. inermis were measured using DPPH (1,1-Diphenyl-2-picrylhydrazyl), FRAP (ferric reducing antioxidant power), and ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6sulfonic acid). Methanol and ethyl acetate extractions of L. inermis leaves and seeds, respectively, demonstrated the highest antioxidant activity in DPPH and FRAP assays. In conclusion, L. inermis extracts have high antioxidant properties and can be useful in both medicine and food industry. Future studies are needed to investigate the most suitable extraction solvents for each part of this valuable plant.